Are “Extracurricular” Activities Really Extracurricular? The Activities That Matter Least in School Are the Ones That Best Teach Real-World Critical and Creative Thinking - Robert J. Sternberg; Sherry Lin; Eric C. K. Nguyen (Journal of Intelligence)
Curricula in school often do not prepare students adequately for the kinds of critical and creative thinking that they will need in their careers and lives. Part of the problem is that the characteristics of real-world problems differ greatly from the characteristics of many curricular activities, and so what the students learn in school about critical and creative thinking may fail when generalized to everyday problems. We suggest that extracurricular activities, such as in aspects of musical and athletic training, often prepare students better for real-world challenges. We describe the kinds of methods that can be used in curricular instruction to better prepare students for the challenges of the everyday world.